PROSES PRODUKSI PRODUK WAJAN BAHAN PLAT BAJA KARBON DENGAN METODE SPINNING - Budi Luwar Sanyoto,; Eddy Widiyono,; Denny ME Soedjono; Nur Husodo, (Jurnal Poli-Teknologi, 2011)
The process of metal spinning is the process of forming sheet metal with a combination of rotary motion and compression force to produce the products according shape mandril. This spinning process has the potential to be applied to small industries producing pan. Because it is necessary for application of the spinning process to form a pan products. Pans that will be realized based carbon steel plate with a shape like a teflon pan. Circular steel plate was placed in front of the mandrill and was gripped by the clamping components assisted by clamping the magnet system. Combination of rotary motion and compression force of the roll will cause the deformation of carbon steel to produce a product. Experiments performed with materials of carbon steel with a thickness of 0.8 mm and 1mm. In conclusion, the calculation of forces on the formation of carbon steel plate with a thickness of 0.8 mm is 14.722 kgf or 144, 277 N, with a thickness of 1 mm of 18.402 kgf or 180, 339 N. The existence of magnetic components will greatly assist the process of clamping plate material so the process of formation by the method of spinning operations become easier in operation. Keywords : pan, spinning process, mandrill, magnetic. ABSTRAK Proses metal spinning adalah proses pembentukan lembaran logam dengan kombinasi gerak putar dan gaya tekan sehingga menghasilkan produk sesuai bentuk mandril. Proses spinning ini sangat berpotensi untuk dapat diterapkan pada industri kecil yang memproduksi produk wajan. Karena itu perlu dilakukan penerapan proses spinning untuk membentuk produk wajan. Wajan yang akan diwujudkan berbahan plat baja karbon dengan bentuk seperti wajan teflon. Plat baja berbentuk lingkaran ditempatkan di depan mandrill dan dicekam dengan komponen clamping dibantu dengan pencekaman dengan system magnit. Kombinasi gerak putar dan gaya tekan dari roll akan menyebabkan deformasi baja karbon sehingga dihasilkan produk. Percobaan dilakukan dengan bahan baja karbon dengan ketebalan 0,8 mm dan 1mm. Kesimpulannya, perhitungan gaya pembentukan pada plat baja karbon dengan tebal 0,8 mm adalah 14,722 Kgf atau 144, 277 N, dengan tebal 1 mm sebesar 18,402 kgf atau 180, 339 N. Adanya komponen magnet akan sangat membantu proses pencekaman bahan plat sehingga proses operasional pembentukan dengan metode spinning menjadi lebih mudah dalam operasional. Kata kunci: wajan, proses spinning, mandill, magnet.